Evaluating performance of construction organizations using fuzzy preference relation technique. Issue 12 (18th October 2021) - Tripathi, Kamalendra Kumar; Hasan, Abid; Neeraj Jha, Kumar
Abstract: Evaluating the performance of construction organizations is of vital importance for their continuous improvement and long-term survival. Performance measurement enables organizations to compare their performance with that of others to remain competitive in the business. Consequently, identification and evaluation of relevant performance measurement factors is an important research agenda. Although performance measurement at the level of projects has been studied in depth, it has not been investigated properly at the level of organization. In an earlier study, the authors had identified 20 performance attributes based on existing literature and grouped them under six performance factors (PFs): profitability and asset management; satisfaction of key stakeholders; predictability of cost and time; environment, health and safety (EHS); quality consciousness and staff turnover . The present study uses consistent fuzzy preference relation (CFPR) to determine the relative weights of these factors and associated performance measurement attributes. The findings indicate that the satisfaction of the key stakeholders is the most important performance measurement factor whereas, staff turnover is the least important factor for performance evaluation. Based on the findings, a user-interface in the form of a user-friendly software has been developed. The interface will help construction organizations in assessing and improving their performance to remain competitive in a highly competitive business environment.